Optimizing Resources in the Implementation of Internal Quality Assurance Systems: An Exploratory Study in Islamic Educational Institutions - Nispi Ani Barus; Alma Vorfi Lama (JUMPA : Jurnal Manajemen Pendidikan, 2024)
This study focuses on the implementation of the Internal Quality Assurance System (SPMI) in Islamic Education Institutions (LPI) and aims to identify the main challenges faced as well as the key factors that can improve the effectiveness of SPMI implementation in these institutions. The research method used is qualitative with a case study approach, where data is collected through in-depth interviews, participatory observations, and document analysis from two LPIs in Yogyakarta. The results show that the gap between SPMI implementation policies and practices in LPI is mostly due to limited resources and low commitment from stakeholders. In addition, strong leadership and continuous support have proven to be important factors in building a sustainable quality culture. The implications of this study emphasize the need for a more holistic management strategy and adequate resource support to ensure that SPMI can function as an effective tool in improving the quality of education in LPI.